Shaking table test and numerical simulation of an RC frame‐core tube structure for earthquake‐induced collapse. (15th March 2016) - Lu, Zheng; Chen, Xiaoyi; Lu, Xilin; Yang, Zi
Summary: The reinforced concrete frame‐core tube structure is a common form of high‐rise building; however, certain vertical components of these structures are prone to be damaged by earthquakes, debris flow, or other accidents, leaving no time for repair or retrofit. This study is motivated by a practical problem—that is, the seismic vulnerability and collapse resistant capability under future earthquakes when a vertical member has failed. A reduced scale model (1:15 scale) of a typical reinforced concrete frame‐core tube with a corner column removed from the first floor is designed, fabricated, and tested. The corner column is replaced by a jack, and the failure behavior is simulated by manually unloading the jack. The model is then excited by a variety of seismic ground motions on the shaking table. Experimental results concerning the seismic responses and actual process of collapse are presented herein. Finally, the earthquake‐induced collapse process is simulated numerically using the software program ANSYS/LS‐DYNA. Validation and calibration of the model are carried out by comparison with the experimental results. Furthermore, based on both experimental investigations and numerical simulations, the collapse mechanism is discussed, and some suggestions on collapse design are put forward. Copyright © 2016 John Wiley & Sons, Ltd.